1973
DOI: 10.1007/bf01249923
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic drift of equine infectious anemia virus in chronically infected horses

Abstract: SummaryHorses e~perimentally infected with a cloned virus of equine infectious anemia (EIA) exhibited a chronical disease with periodical relapses of fever and simultaneously increased viremia. Virus isolates taken at successive febrile attacks proved to be changed in their antigenic specificity. These virus variants could be differentiated from one another by neutralizing, but not complement-fi~ing or precipitating antibodies, suggesting a modification of surface antigens only. No alteration of infectivity am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 12 publications
4
119
0
Order By: Relevance
“…These serial passage experiments are described in detail in Orrego et al (1982). serological uniqueness of virus isolates recovered from sequential febrile episodes (Orrego, 1983 ;Montelaro et al, 1984), thereby confirming the reports of Kono et al (1971Kono et al ( , 1973. Biochemical analyses indicated structural variations in the glycoproteins of the virus isolates examined, presumably correlating with the antigenic variations revealed in neutralization studies (Montelaro et al, 1984).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These serial passage experiments are described in detail in Orrego et al (1982). serological uniqueness of virus isolates recovered from sequential febrile episodes (Orrego, 1983 ;Montelaro et al, 1984), thereby confirming the reports of Kono et al (1971Kono et al ( , 1973. Biochemical analyses indicated structural variations in the glycoproteins of the virus isolates examined, presumably correlating with the antigenic variations revealed in neutralization studies (Montelaro et al, 1984).…”
Section: Discussionsupporting
confidence: 70%
“…Horses infected with EIAV develop neutralizing antibody against the predominant virus while continuing to experience bursts of viraemia. Previous neutralization studies have indicated that the periodic and persistent nature of the disease may be due to the sequential production and release of novel antigenic strains of the virus capable of escaping host immunosurveillance systems (Kono, 1973;Kono et al, 1971Kono et al, , 1973. However, there have been no published studies confirming these neutralization studies or characterizing the nature of the viral variants.…”
Section: Discussionmentioning
confidence: 64%
“…This phenomenon is well known with several virus types, including influenza virus (Laver & Webster, 1968), foot-and-mouth disease virus (Hyslop & Fagg, 1965) and lentiviruses such as equine infectious anaemia virus (Kono et al, 1973;Crawford et al, 1978) and maedi-visna virus (Petursson et aL, 1976;Narayan et al, 1977a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on EIAV have shown that the virus mutates at random and mutants are selected by specific antibodies. Emergence of new, non-neutralizable viruses coincides with cyclical episodes of disease in horses (Kono et al, 1973). Antigenic variation also occurs during the persistent infection of sheep with visna virus (Narayan et al, 1977a, b) and probably also in humans infected with HIV .…”
Section: Antigenic Variationmentioning
confidence: 99%
“…Mutations are associated frequently with the development of neutralization-escape variants. Under the selective pressure of antibodies described above, variants of visna virus, EIAV, and more recently HIV, have been obtained easily Kono et al, 1973;Kono, 1988;Reitz et al, 1988).…”
Section: Viral Antigensmentioning
confidence: 99%